Comparative quantative analysis of zinc, magnesium, and copper content in the scalp hair of healthy people and breast cancer patients - Kilic, E; Demiroğlu-Zergeroğlu, Asuman; Saraymen, R; Ok, E (Wiley-Liss, 2004)
A quantitative elemental analysis of scalp hair of female breast cancer patients (n = 26) and female controls (n = 27) was used to Study to find out correlation and possible changes. between breast cancer and healthy controls. Atomic absorption spectrophotometer analysis of the quantitative method was used to determine copper, magnesium, and zinc levels. There were no differences in magnesium concentrations (P > 0.05) in breast cancer patients and healthy subjects. However, comparison of mean elemental contents of the breast cancer patients with controls showed a significant enhancement of copper (P < 0.05) but declining trends for zinc (P < 0.05) in breast cancer patients. The usefulness and significance of element status in cancer patients should be discussed more detailed in the light of the most these recent data. (C) 2004 Wiley-Liss, Inc.
Keywords: breast cancer; hair; trace element; atomic absorption spectrophotometer